The effectiveness of using role play videos to enhance students' speaking performance: a case study of UiTM Cawangan Kelantan interim students / Anis Idayu Aziz... [et al.] - Aziz, Anis Idayu; Raja Yacob, Raja Nur Hidayah; Abd Razak, Amanina; Suhaimin, Mohd Faiez (Universiti Teknologi Mara Cawangan Kelantan, 2020)
Speaking competence marks an evident proof of success in the process of second language acquisition. Hence, the syllabus of speaking has become a burgeoning aspect of many English courses. Realizing the importance of speaking fluency and accuracy in the target language, language professionals and instructors have never stopped to find practical ways to enhance the learners' speaking skill. Reflecting upon the many sessions of teaching English to students at UiTM Kelantan Branch, more often than not, the students admitted to having fear in speaking lessons as compared to lessons on other skills. They find it difficult to express their feelings in the target language as their native language stands as a barrier. This has prompted some language instructors to put much effort into providing various communicative activities to help students overcome their fear, among which is through role-play activities. In this study, role-plays are compiled in the form of video recordings and prepared as supplementary material for both teachers and students to be used in and out of classrooms. The research's main objective is to determine the relationship between the effectiveness of role-play videos and students' speaking performance. 127 respondents of the interim semester at UiTM Kelantan Branch were selected as the samples for this research. Simple random sampling was used, and questionnaires were distributed for data collection. The finding shows that the correlation value between the effectiveness of role play videos and students' speaking performance is 0.933 (p=0.000 < 0.05). Thus, this means there is a significant, strong positive relationship between the effectiveness of role play videos and students' speaking performance